Dokumentarische Evaluationsforschung Theoretische Grundlagen und Beispiele Aus der Praxis. - Thiersch, Sven (Verlag Barbara Budrich, 2020)
Documentary evaluation research follows the tradition of the documentary method of Karl Mannheim and Ralf Bohnsack and is methodologically and practically inspired by approaches of qualitative evaluation from the United States. This book demonstrates the methodological potential of a variety of evaluation objects in research practice.